IMPROVING THE WEAR RESISTANCE OF STRUCTURAL STEELS BY ELECTROSPARK DEPOSITION - Mikosianchyk, Oksana; Skvortsov, Oleksandr; Kornienko, Anatolii (Problems of Friction and Wear, 2025)
The advantages of the electrospark deposition method in forming wear-resistant coatings on steel parts have been analyzed, and the main requirements for electrode materials for forming coatings with high hardness, wear resistance, and crack resistance have been identified. The aim of this work was to assess the wear resistance of electrospark coatings made from high-carbon steel U10 (DIN: 1.1645) and high-speed steel R18 (DIN: 1.3355) on structural steels in an abrasive environment. It was found that for uncoated structural steels, weight loss due to abrasion decreases with increasing material hardness. This is caused by improved abrasion resistance in steel 45 due to a higher proportion of iron carbides, and in medium-alloy steel 30ХГСА due to deposition carbide-forming elements such as manganese and chromium. The enhancement in wear resistance of structural steels with electrospark coatings is substantiated by the more effective resistance of hardened surface layers under abrasive particle impact, which is due to the formation of coatings with a high content of Fe carbides (U10 and R18 coatings), W, Cr, and V carbides (R18 coatings). The possibility of controlling structural effects and phase composition of modified surface layers of structural steels by applying electrospark coatings with the required level of tribotechnical properties has been demonstrated.